Papers presented at the FAO / NACA consultation on aquaculture for sustainable rural development, Chiang Rai, Thailand, 29 - 31 March 1999 (FAO/NACA, 2005)
This document contains the papers presented at the Consultation on Aquaculture for Sustainable Rural Development which was organized jointly by FAO and NACA and held in Chiang Rai, Thailand, from 29 to 31 March 1999 in order to develop the detailed structure of a regional program on aquaculture for sustainable rural development and to propose a strategy for its implementation. The consultation took an overview of the relevant information emerging from the presentations of country reports; lessons learned by specific projects; experiences of regional and international organizations and donor agencies; and findings of expert reviews.